Identification of Plastoglobules as a Site of Carotenoid Cleavage - Rottet, Sarah; Devillers, Julie; Glauser, Gaétan; Douet, Véronique; Besagni, Céline; Kessler, Felix (Frontiers in Plant Science, 2016)
Carotenoids play an essential role in light harvesting and protection from excess light. During chloroplast senescence carotenoids are released from their binding proteins and are eventually metabolized. Carotenoid cleavage dioxygenase 4 (CCD4) is involved in carotenoid breakdown in senescing leaf and desiccating seed, and is part of the proteome of plastoglobules (PG), which are thylakoid-associated lipid droplets. Here, we demonstrate that CCD4 is functionally active in PG. Leaves of Arabidopsis thaliana ccd4 mutants constitutively expressing CCD4 fused to YFP showed strong fluorescence in PG and reduced carotenoid levels upon dark-induced senescence. Lipidome-wide analysis indicated that β-carotene, lutein and violaxanthin were the principle substrates of CCD4 in vivo and were cleaved in senescing chloroplasts. Moreover, carotenoids were shown to accumulate in PG of ccd4 mutant plants during senescence, indicating translocation of carotenoids to PG prior to degradation.